Preparation method of two-dimensional vanadium-based oxide heterojunction material and application of two-dimensional vanadium-based oxide heterojunction material in rechargeable zinc ion battery
By preparing two-dimensional vanadium-based oxide heterojunction material and combining graphene self-assembly technology, the problem of easy soluble and easy structure collapse during the charging and discharge process of zinc ion battery is solved, and a positive electrode material with high capacity and high stability is achieved, which significantly improves the cycling performance of zinc ion battery.
Patent Information
- Application Number
- CN202311221196.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-20
- Publication Date
- 2025-03-21
AI Technical Summary
The positive electrode material of zinc ion battery is easily soluble in water during charging and discharging, and the structure is prone to collapse, resulting in capacity attenuation and instability problems.
A two-dimensional vanadium-based oxide heterojunction material is used to form a high-stability two-dimensional structure by reacting vanadium-based compounds with ammonia salt compounds and sodium salt compounds under hydrothermal conditions, combined with self-assembly technology of graphene or graphene oxide.
It has achieved high capacity and high stability of the positive electrode material of zinc ion battery, excellent circulation performance, and capacity retention rate of up to 85%.
Smart Images

Figure HDA0004460671060000011 
Figure HDA0004460671060000012 
Figure HDA0004460671060000021
Abstract
Description
Technical Field
[0001] The invention belongs to the field of zinc ion batteries and relates to a preparation method of a two-dimensional vanadium-based oxide heterojunction material and an application of the same in a rechargeable zinc ion battery. Background Art
[0002] The use of renewable energy such as wind and solar energy can greatly reduce CO2 emissions. However, its intermittent, volatile, random and regional dependence make energy storage regulation the key to its widespread application. Compared with traditional mechanical energy storage, electromagnetic energy storage, thermal energy storage and chemical energy storage, electrochemical energy storage (i.e. secondary battery energy storage) will play an important role in the future energy storage market due to its flexible layout and high technical maturity (Science, 2011, 334, 928). However, my country's existing battery energy storage has experienced fire accidents of varying degrees on the grid side, power generation side and user side. Therefore, the development of high-safety, long-life and low-cost energy storage battery technology is an important research direction in the future.
[0003] my country has abundant reserves of zinc metal (ranking first in the world), which has the advantages of low cost (2.4$ / kg), non-toxicity and high theoretical capacity (5851mAh / mL; 820mAh / g) (Chem. Rev., 2014, 114, 11683). Its relatively low redox potential (-0.76V vs SHE) makes it possible to directly use water-based electrolytes with high ionic conductivity. Thanks to the relatively stable chemical and physical properties of zinc metal, aqueous zinc batteries have no risk of explosion or fire, and their high safety makes them have great potential in the field of energy storage. In March 2021, the International Zinc Association (IZA) launched the zinc battery as a future energy storage battery plan. Eos Energy Enterprises, a Nasdaq-listed energy storage system designer and manufacturer, also announced in 2021 that it will provide zinc battery energy storage systems for three large-scale battery energy storage projects planned to be deployed in the United States and India. Therefore, aqueous zinc batteries have broad application prospects in the field of large-scale energy storage.
[0004] In aqueous zinc-ion batteries, zinc deposition and dissolution occur on the negative electrode side; on the positive electrode side, H + / Zn 2+ Insertion / extraction in the positive electrode material. 2+ With a high charge density, it will produce electrostatic interaction with the positive electrode material. This leads to Zn 2+ It diffuses slowly in the lattice and easily accumulates in the structure, causing phase changes in the structure and dissolution of active substances, ultimately causing capacity decay. Therefore, the development of highly stable positive electrode materials is one of the key scientific issues for the practical application of zinc-ion batteries. Summary of the invention
[0005] The present invention aims to provide a solution to the instability problems of zinc ion battery positive electrode materials being slightly soluble in water and the structure being easy to collapse during charging and discharging. To this end, the present invention systematically provides a method for preparing a high-capacity, highly stable two-dimensional vanadium-based oxide heterojunction material and its application in a rechargeable zinc ion battery.
[0006] First, the present invention provides a method for preparing a two-dimensional vanadium-based oxide heterojunction material, wherein the chemical composition of the two-dimensional vanadium-based oxide heterojunction material is M x V6O 16 ·nH2O / G, wherein M is one or more of Zn, Mg, Cu, and Ca, x is 0.8 to 1.1, n is 1 to 9, and G is graphene or graphene oxide. The preparation method comprises the following steps: firstly dispersing a vanadium-based compound and one or more of an ammonium salt compound, a sodium salt compound, and a potassium salt compound in an aqueous solution; adjusting the pH of the mixed solution to 1 to 3 with an appropriate amount of an acidic solution to obtain a solution A; then reacting the solution A under hydrothermal conditions at a certain temperature for a period of time; obtaining a precursor 1 through centrifugation or filtration, washing, and drying; then immersing the precursor 1 in a salt solution of a certain concentration of M at a certain temperature for a period of time to cause ion exchange; and obtaining a precursor 2 through centrifugation or filtration, washing, and drying. Precursor 2 is dispersed in an organic solvent and ball-milled at a certain speed for a period of time to obtain solution B, graphene or graphene oxide is added to B and further exfoliation is promoted by ultrasound to obtain solution C, and solution C is reacted at a certain temperature under solvent thermal conditions for a period of time to allow it to self-assemble; a two-dimensional vanadium-based oxide heterojunction material is obtained after centrifugation or filtration, washing and drying.
[0007] Furthermore, in the above technical solution, the vanadium-based compound is one or more of vanadium pentoxide, vanadium dioxide, vanadyl sulfate and ammonium metavanadate; and the concentration of the vanadium-based compound is 0.01 to 1 mol / L.
[0008] Furthermore, in the above technical solution, the ammonia, sodium and potassium salt compounds are one or more of NH4F, (NH4)2SO4, NH4NO3, NH4Cl, NH4Ac, (NH4)2CO3, NaF, Na2SO4, NaNO3, NaCl, NaAc, Na2CO3, KF, K2SO4, KNO3, KCl, KAc, K2CO3; the preferred ammonia, sodium and potassium compounds are NH4Cl, NaF and KCl. The concentration of the ammonia, sodium and potassium salt compounds is 0.01-1 mol / L; when the vanadium-based compound is ammonium metavanadate, the concentration of the ammonia, sodium and potassium salt compounds is 0-1 mol / L.
[0009] Furthermore, in the above technical solution, the acidic solution is one or more of hydrochloric acid, sulfuric acid, nitric acid, glacial acetic acid, and hydrogen peroxide.
[0010] Furthermore, in the above technical solution, the reaction temperature of the precursor 1 is 120-200°C, and the reaction time is 2-48h. The preferred reaction temperature is 160-180°C; the preferred reaction time is 18-36h.
[0011] Furthermore, in the above technical solution, the metal ion M in the salt solution of M is one or more of Zn, Mg, Cu, and Ca, and the preferred metals are Zn and Mg; the sum of the concentrations of the metal ions is 0.1 to 4 mol / L;
[0012] Further, in the above technical solution, the salt solution of M is one or more of MSO4, M(NO3)2, M(Ac)2, MCl2, M(ClO4)2; preferably MSO4 and M(NO3)2 solution;
[0013] Furthermore, in the above technical solution, the ion exchange reaction temperature is -5 to 100°C, and the reaction time is 1 to 20 days; the preferred reaction temperature is 15 to 30°C; and the preferred reaction time is 1 to 5 days.
[0014] Furthermore, in the above technical solution, the organic solvent is one or more of methanol, ethanol, isopropanol, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide; preferably N-methylpyrrolidone;
[0015] Furthermore, in the above technical scheme, the reaction temperature of the two-dimensional vanadium-based oxide heterojunction material is 120-200°C, and the reaction time is 1-20 days; the preferred reaction temperature is 160-180°C; the preferred reaction time is 1-5 days; the mass ratio of precursor 2 to graphene or graphene oxide is 2-5.
[0016] The present invention provides a two-dimensional vanadium-based oxide heterojunction material prepared by the method, which is used as a positive electrode of a zinc ion battery and exhibits excellent cycle stability; the preparation steps of the zinc ion battery positive electrode sheet are: dispersing the two-dimensional vanadium-based oxide heterojunction material, activated carbon and polyvinylidene fluoride in N-methylpyrrolidone, mixing them evenly to form a slurry, applying it to a current collector, and vacuum drying at 40 to 120° C. for 5 to 48 hours to obtain a zinc ion battery positive electrode sheet.
[0017] Furthermore, in the above technical solution, the mass ratio of the two-dimensional vanadium-based oxide heterojunction material, activated carbon and polyvinylidene fluoride is (6-8):(1-3):1.
[0018] Furthermore, in the above technical solution, the current collector is a stainless steel mesh, a stainless steel foil, a titanium mesh or a titanium foil.
[0019] Furthermore, in the above technical solution, the loading amount of the active material of the positive electrode of the zinc ion battery is 0.5-10 mg cm -2 The preferred positive electrode active material loading is 1-5 mg cm -2 .
[0020] Furthermore, in the above technical solution, the vacuum drying temperature is 40-120°C, and the vacuum drying time is 5-48 hours. The preferred vacuum drying temperature is 60-80°C, and the preferred vacuum drying time is 10-24 hours.
[0021] Finally, the two-dimensional vanadium-based oxide heterojunction material positive electrode sheet is assembled in a zinc ion battery. The preparation steps of the zinc ion battery are to place the two-dimensional vanadium-based oxide heterojunction material positive electrode sheet and zinc foil in a battery shell, put a separator in the middle, add an electrolyte containing zinc ions, and then package the battery. The packaged battery is connected to an electrochemical charge and discharge instrument to perform a cycle performance test at a specified current density.
[0022] Beneficial results:
[0023] The preparation method of the two-dimensional vanadium-based oxide heterojunction material requires simple equipment, is easy to operate, and has low cost. The X-ray diffraction (XRD) spectrum shows that the XRD spectrum of the two-dimensional vanadium-based oxide heterojunction material obtained by the present invention has low crystallinity (see Figure 1 ). Transmission electron microscopy shows that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet-like microstructure (see Figure 2 ). Zinc-ion batteries based on two-dimensional vanadium-based oxide heterojunction material positive electrode sheets have a 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 412 mAh g -1 (See Figure 3 ), at 0.3Ag -1 After 130 cycles, the capacity retention rate is still as high as 85% (see Figure 4 ). BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention is attached Figure 5 Size:
[0025] Figure 1 is the XRD spectrum of the two-dimensional vanadium-based oxide heterojunction material prepared in Example 1;
[0026] Figure 2 is a transmission electron microscope image of the two-dimensional vanadium-based oxide heterojunction material in Example 1;
[0027] Figure 3is a charge and discharge curve diagram of the two-dimensional vanadium-based oxide heterojunction material as the positive electrode zinc ion battery in Example 1;
[0028] Figure 4 is a long-term cycle performance diagram of the two-dimensional vanadium-based oxide heterojunction material as a positive electrode zinc ion battery in Example 1;
[0029] Figure 5 1 is the XRD spectrum of the two-dimensional vanadium-based oxide heterojunction material prepared in Examples 1 to 10. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a two-dimensional vanadium-based oxide heterojunction material, and application of the two-dimensional vanadium-based oxide heterojunction material obtained by the method as a positive electrode material in a rechargeable zinc ion battery. The chemical composition of the two-dimensional vanadium-based oxide heterojunction material is M x V6O 16 nH2O / G, wherein M is one or more of Zn, Mg, Cu, and Ca, x is 0.8 to 1.1, n is 1 to 9, and G is graphene or graphene oxide.
[0031] The following examples will further illustrate the present invention, but are not intended to limit the invention.
[0032] The method for preparing the two-dimensional vanadium-based oxide heterojunction material in the following embodiments 1-9 comprises the following steps:
[0033] (1) A certain amount of vanadium-based compound and ionic salt compound are dispersed in a certain amount of aqueous solution.
[0034] (2) Add a certain amount of acidic solution to the mixed solution of step (1) and adjust the pH value to obtain solution A.
[0035] (3) Transfer solution A in step (2) to a stainless steel reactor lined with polytetrafluoroethylene and react at high temperature for a period of time.
[0036] (4) The turbid system obtained after the reaction in step (3) is centrifuged or filtered, washed with water and ethanol, and dried to obtain precursor 1.
[0037] (5) Immersing the precursor obtained in step (4) in a salt solution of a certain concentration to cause ion exchange.
[0038] (6) The turbid system in step (5) is centrifuged or filtered, washed with water and ethanol, and dried to obtain precursor 2.
[0039] (7) Precursor 2 in step (6) is dispersed in an organic solvent and ball-milled to obtain solution B.
[0040] (8) Adding solution B in step (7) to graphene / graphene oxide and performing ultrasound treatment to obtain solution C.
[0041] (9) The solution C in step (8) is transferred to a stainless steel reactor lined with polytetrafluoroethylene and reacted at high temperature for a period of time.
[0042] The method for preparing the two-dimensional vanadium-based oxide heterojunction material positive electrode sheet in the following embodiments 1-9 comprises the following steps:
[0043] (1) Weigh a certain mass of two-dimensional vanadium-based oxide heterojunction material, activated carbon and polyvinylidene fluoride.
[0044] (2) Add an appropriate amount of N-methylpyrrolidone and grind for 2 h to obtain a slurry.
[0045] (3) After the slurry is coated on the current collector, it is dried in a vacuum oven at a certain temperature for a period of time to obtain a two-dimensional vanadium-based oxide heterojunction material positive electrode sheet.
[0046] The preparation method of the zinc ion battery in the following embodiments 1-9 comprises the following steps:
[0047] A two-dimensional vanadium-based oxide heterojunction material positive electrode sheet and a zinc foil negative electrode are placed in a battery shell, a glass fiber separator is placed in the middle, a ZnSO4 (2M) aqueous solution is added, and then the battery is packaged to produce a rechargeable zinc ion battery.
[0048] The performance of the zinc ion battery prepared in the embodiment of the present invention was further evaluated by testing its long-term cycle performance at a specific current density and an operating voltage range of 0.2V to 1.6V.
[0049] Example 1
[0050] Weigh 0.234g NH4VO3 in a beaker, add 30mL deionized water to obtain a yellow suspension, add 5mL H2O2 and 10 drops of concentrated nitric acid to adjust the pH to 2 to obtain solution A. Then transfer solution A to a reactor and react at 160℃ for 18h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish-brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL ZnSO4 (2M) aqueous solution, stir at 25℃ for 24h. Then wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL N-methylpyrrolidone and ball mill at 60r / min for 12h to obtain solution B. 0.02 g of graphene was added to solution B and ultrasonically promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 180°C for 12 h. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60°C for 12 h to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2 (see Figure 1 ). Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Zn 0.89 V6O 16 ·2.7H2O. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet-like microstructure (see Figure 2 ). Weigh 0.15g black powder, 0.03g conductive carbon black (Super P) and 0.02g XC-72 into a mortar, add 1mL N-methylpyrrolidone, grind for 2h to mix evenly to obtain electrode slurry. Then apply the above electrode slurry on a stainless steel current collector with a diameter of 14mm and dry it in a vacuum oven at 100℃. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 412 mAh g -1 (See Figure 3 ), at 0.3Ag -1 After 130 cycles, the capacity retention rate is still as high as 86% (see Figure 4 ).
[0051] Example 2
[0052] Weigh 0.91g V2O5 and 0.63g NaF in a beaker, add 70mL deionized water to obtain a yellow suspension, and stir for 2 minutes to obtain solution A. Then transfer solution A to a reactor and react at 180℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish-brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL ZnSO4 (2M) aqueous solution, stir at 25℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL dimethylformamide and ball mill at 60r / min for 12h to obtain solution B. Add graphene to solution B and perform ultrasonic-promoted exfoliation to obtain solution C. Solution C was then transferred to a reactor and reacted at 180°C for 12 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60°C for 12 hours to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Zn 0.94 V6O 16 ·1.6H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 408 mAh g -1 , at 0.3Ag -1 The capacity retention rate after 130 cycles is still as high as 84%.
[0053] Example 3
[0054] Weigh 1g V2O5 in 15mL (2M) KCl aqueous solution in a beaker, stir at 35℃ for 6h to accelerate the reaction rate, then continue to stir at room temperature for 80h, finally wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL ZnSO4 (2M) aqueous solution, stir at 25℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL dimethylacetamide and ball mill at 60r / min for 12h to obtain solution B. Graphene is added to solution B and ultrasonically promoted exfoliation is performed to obtain solution C. Then solution C is transferred to a reactor and reacted at 180℃ for 12h. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60 ° C for 12 hours to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Zn 0.96 V6O 16 ·4H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 404 mAh g -1 , at 0.3Ag -1 The capacity retention rate after 130 cycles is still as high as 83%.
[0055] Example 4
[0056] Weigh 0.182g V2O5 and 0.056g KNO3 in a beaker, add 30mL deionized water to dissolve, stir for 30min to form solution A, then transfer solution A to the reactor and react at 200℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL ZnSO4 (2M) aqueous solution, stir at 25℃ for 36h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL dimethyl sulfoxide solvent and ball mill at 60r / min for 12h to obtain solution B. Add graphene to solution B and perform ultrasonic-promoted exfoliation to obtain solution C. Solution C was then transferred to a reactor and reacted at 180°C for 12 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60°C for 12 hours to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Zn 1.05 V6O 16 ·5.2H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 403 mAh g -1 , at 0.3Ag -1 The capacity retention rate after 130 cycles is still as high as 82%.
[0057] Example 5
[0058] Weigh 0.234g NH4VO3 and dissolve it in 50mL deionized water, add 0.053g Na2CO3 and stir for 30min, then add 1mL H2O2 and 10 drops of hydrochloric acid to adjust the pH to about 1.9 to obtain solution A, then transfer solution A to the reactor and react at 200℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL MgSO4 (2M) aqueous solution, stir and react at 25℃ for 48h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL N-methylpyrrolidone and ball mill at 60r / min for 18h to obtain solution B. Graphene was added to solution B and ultrasonically promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 180°C for 18 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60°C for 12 hours to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy analysis and thermogravimetric analysis showed that the black powder was Mg 0.86 V6O 16 ·4H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.5 %, the specific capacity can reach 405 mAh g -1 , at 0.3Ag -1 The capacity retention rate after 130 cycles is still as high as 81%.
[0059] Example 6
[0060] Weigh 0.234g NH4VO3 in a beaker, add 30mL deionized water to obtain a yellow suspension, add 0.04g NH4NO3 and stir for 30min, add 5mL H2O2 and 10 drops of concentrated nitric acid to adjust the pH to 2 to obtain solution A. Then transfer solution A to a reactor and react at 160℃ for 18h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish-brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL CuSO4 (2M) aqueous solution, stir at 25℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL N-methylpyrrolidone and ball mill at 60r / min for 12h to obtain solution B. Graphene oxide was added to solution B and ultrasonically promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 180°C for 24 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. Drying in a vacuum oven at 60°C for 12 hours gave a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Cu 0.91 V6O 16 ·5H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 403 mAh g -1 , at 0.3Ag -1 The capacity retention rate after 130 cycles is still as high as 84%.
[0061] Example 7
[0062] Weigh 0.234g NH4VO3 in a beaker, add 30mL deionized water to obtain a yellow suspension, add 0.05g NaNO3 and stir for 30min, add 5mL H2O2 and 10 drops of concentrated nitric acid to adjust the pH to 2 to obtain solution A. Then transfer solution A to a reactor and react at 160℃ for 18h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish-brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL Ca(NO3)2(1M) aqueous solution, stir and react at 25℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. 0.1 g of precursor 2 powder was dispersed in 100 mL of N-methylpyrrolidone and ball-milled at 60 r / min for 12 h to obtain solution B. Graphene oxide was added to solution B and ultrasonic-promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 160°C for 24 h. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol 3 times and centrifuged. Drying in a vacuum oven at 60°C for 12 h gave a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with that of precursor 2. Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Ca 0.95 V6O 16 ·6.2H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 409 mAh g -1 , at 0.5Ag -1 The capacity retention rate after 300 cycles is still as high as 85%.
[0063] Example 8
[0064] Weigh 0.234g NH4VO3 in a beaker, add 30mL deionized water to obtain a yellow suspension, add 0.06g (NH4) 2SO4 and stir for 30min, add 5mL H2O2 and 10 drops of concentrated nitric acid to adjust the pH to 2 to obtain solution A. Then transfer solution A to a reactor and react at 180℃ for 24h. Finally, wash with water to pH = 7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL ZnSO4 (2M) aqueous solution, stir at 80℃ for 48h. Finally, wash with water to pH = 7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL methanol and ball mill at 60r / min for 24h to obtain solution B. Graphene oxide was added to solution B and ultrasonically promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 180°C for 24 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60°C for 12 hours to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy analysis and thermogravimetric analysis showed that the black powder was Zn 1.01 V6O 16 ·7.2H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (SuperP) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then apply the above electrode slurry on a stainless steel current collector with a diameter of 14mm and dry it in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3A g -1 At a current density of 1.34 W, the specific capacity can reach 402 mAh g -1 , at 0.3A g -1 The capacity retention rate after 130 cycles is still as high as 81%.
[0065] Example 9
[0066] Weigh 0.234g NH4VO3 in a beaker, add 30mL deionized water to obtain a yellow suspension, add 0.03g KF and stir for 30min, add 5mL H2O2 and 10 drops of concentrated nitric acid to adjust the pH to 2 to obtain solution A. Then transfer solution A to a reactor and react at 160℃ for 18h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish-brown precursor 1 powder. Take 0.2g of the precursor powder and 50mL of ZnSO4 (1M) aqueous solution, stir at 25℃ for 48h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of the precursor 2 powder and disperse it in 100mL N-methylpyrrolidone and ball mill at 60r / min for 48h to obtain solution B. Graphene was added to solution B and ultrasonically promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 200°C for 12 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. Drying in a vacuum oven at 60°C for 12 hours gave a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy and thermogravimetric analysis showed that the black powder was Zn 1.06 V6O 16 ·8.1H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. The above electrode slurry is then coated on a stainless steel current collector with a diameter of 14mm and dried in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3Ag -1 At a current density of 1.34 W, the specific capacity can reach 402 mAh g -1 , at 0.3A g -1 The capacity retention rate after 130 cycles is still as high as 81%.
[0067] Example 10
[0068] Weigh 0.234g NH4VO3 in a beaker, add 30mL deionized water to obtain a yellow suspension, add 0.06g NH4F and stir for 30min, add 5mL H2O2 and 10 drops of concentrated nitric acid to adjust the pH to 2 to obtain solution A. Then transfer solution A to a reactor and react at 180℃ for 24h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a reddish-brown precursor 1 powder. Take 0.2g of precursor 1 powder and 50mL ZnSO4 (2M) aqueous solution, stir at 80℃ for 48h. Finally, wash with water to pH=7, then wash with anhydrous ethanol 3 times and centrifuge. Dry in a vacuum oven at 60℃ for 12h to obtain a dark red precursor 2 powder. Take 0.1g of precursor 2 powder and disperse it in 100mL N-methylpyrrolidone and ball mill at 80r / min for 48h to obtain solution B. Graphene oxide was added to solution B and ultrasonically promoted exfoliation was performed to obtain solution C. Solution C was then transferred to a reactor and reacted at 200°C for 36 hours. Finally, it was washed with water until pH = 7, then washed with anhydrous ethanol three times and centrifuged. It was dried in a vacuum oven at 60°C for 12 hours to obtain a black two-dimensional vanadium-based oxide heterojunction material powder. X-ray diffraction (XRD) results showed that its crystallinity was significantly reduced compared with precursor 2. Inductively coupled plasma (ICP) spectroscopy analysis and thermogravimetric analysis showed that the black powder was Zn 1.1 V6O 16 ·9H2O / G. Transmission electron microscopy results show that the prepared two-dimensional vanadium-based oxide heterojunction material presents a nanosheet microscopic morphology. Weigh 0.15g of black powder, 0.03g of conductive carbon black (Super P) and 0.02g of XC-72 in a mortar, add 1mL of N-methylpyrrolidone, and grind for 2h to mix evenly to obtain an electrode slurry. Then apply the above electrode slurry on a stainless steel current collector with a diameter of 14mm and dry it in a vacuum oven at 100°C. The obtained positive electrode sheet is used to obtain a zinc ion battery according to the battery preparation method in the above specific implementation method, and the battery performance is evaluated. The test results show that at a current density of 0.3A g -1 At a current density of 1.5 %, the specific capacity can reach 400 mAh g -1 , at 0.3A g -1 The capacity retention rate after 130 cycles is still as high as 81%.
Claims
1. A method for preparing a two-dimensional vanadium-based oxide heterojunction material, characterized in that: The chemical composition of the two-dimensional vanadium-based oxide heterojunction material is M x V6O 16 nH2O / G, wherein M is one or more of Zn, Mg, Cu, and Ca, x is 0.8 to 1.1, n is 1 to 9, and G is graphene or graphene oxide; The preparation method comprises the following steps: 1) First, a vanadium-based compound and one or more of an ammonium salt compound, a sodium salt compound and a potassium salt compound are dispersed in an aqueous solution; the pH of the mixed solution is adjusted to 1-3 with an appropriate amount of an acidic solution to obtain a solution A; then, the solution A is reacted at a certain temperature under hydrothermal conditions for a period of time; and a precursor 1 is obtained by centrifugation or filtration, washing and drying; 2) Then, the precursor 1 is immersed in a salt solution of M with a certain concentration at a certain temperature for a period of time to allow ion exchange to occur; the precursor 2 is obtained by centrifugation or filtration, washing, and drying; 3) Precursor 2 is dispersed in an organic solvent and ball-milled at a certain speed for a period of time to obtain solution B, graphene or graphene oxide is added to B and further exfoliated by ultrasound to obtain solution C, and solution C is reacted at a certain temperature under solvent thermal conditions for a period of time to allow it to self-assemble; a two-dimensional vanadium-based oxide heterojunction material is obtained by centrifugation or filtration, washing, and drying.
2. The preparation method according to claim 1, characterized in that: In the preparation of the precursor 1, the vanadium-based compound is selected from one or more of vanadium pentoxide, vanadium dioxide, vanadyl sulfate and ammonium metavanadate; and the concentration of the vanadium-based compound is 0.01 to 1 mol / L.
3. The preparation method according to claim 1 or 2, characterized in that: In the preparation of precursor 1, the ammonium salt compound is selected from one or more of NH4F, (NH4)2SO4, NH4NO3, NH4Cl, NH4Ac, (NH4)2CO3; the sodium salt compound is selected from one or more of NaF, Na2SO4, NaNO3, NaCl, NaAc, Na2CO3; the potassium salt compound is selected from one or more of KF, K2SO4, KNO3, KCl, KAc, K2CO3; the concentration of the ammonium salt compound, sodium salt compound and potassium salt compound is 0.01~1mol / L; when the vanadium-based compound is ammonium metavanadate, the concentration of the ammonia, sodium and potassium salt compounds is 0~1mol / L.
4. The preparation method according to claim 1, characterized in that: In the preparation of precursor 1, the acidic solution is one or more of hydrochloric acid, sulfuric acid, nitric acid, glacial acetic acid, and hydrogen peroxide; in the preparation of precursor 1, the temperature of the hydrothermal reaction is 120-200° C., and the reaction time is 2-48 hours.
5. The preparation method according to claim 1, characterized in that: In the preparation of precursor 2, the metal ion M in the salt solution of M is one or more of Zn, Mg, Cu, and Ca; the sum of the concentrations of the metal ions Zn, Mg, Cu, and Ca in the salt solution of M is 0.1 to 4 mol / L; in the preparation of precursor 2, the salt solution of M is one or more of MSO4, M(NO3)2, M(Ac)2, MCl2, and M(ClO4)2 solutions.
6. The preparation method according to claim 1, characterized in that: In the preparation of the precursor 2, the mass ratio of the precursor to the salt solution of M is 0.01-2.
7. The preparation method according to claim 1, characterized in that: In the preparation of the precursor 2, the soaking temperature is -5 to 100° C., and the soaking time is 1 to 20 days.
8. The method for preparing a two-dimensional vanadium-based oxide heterojunction material according to claim 1, characterized in that: The organic solvent is one or more of methanol, ethanol, isopropanol, N-methylpyrrolidone, dimethylformamide, dimethylacetamide, and dimethyl sulfoxide.
9. The method for preparing a two-dimensional vanadium-based oxide heterojunction material according to claim 1, characterized in that: The mass ratio of the precursor 2 to graphene or graphene oxide is 2-5; the temperature of the solvent thermal reaction is 120-200° C., and the reaction time is 2-48 hours.
10. Application of the two-dimensional vanadium-based oxide heterojunction material obtained according to the preparation method of claim 1 in a rechargeable zinc-ion battery, wherein the two-dimensional vanadium-based oxide heterojunction material is used as a positive electrode material for a rechargeable zinc-ion battery.